2004
DOI: 10.1016/j.jchromb.2004.03.079
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of 33 benzodiazepines, metabolites and benzodiazepine-like substances in whole blood by liquid chromatography?(tandem) mass spectrometry

Abstract: A quantitative method using high-performance liquid chromatography-mass spectrometry (LC-MS, ion trap) after matrix supported liquid-liquid extraction is described for the simultaneous determination in whole blood of 33 benzodiazepines including metabolites and benzodiazepine-like substances. The limits of detection (LOD) range from 0.0001 to 0.0126 mg/l. Linearity is satisfactory for all compounds. The extraction recoveries for the benzodiazepines in whole blood are between 60 and 91%, desmethyldiazepam, OH-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 13 publications
4
22
0
1
Order By: Relevance
“…On the basis of the proposed fragmentation pathway for the metabolite temazepam m/z 301.0, it is possible to form the m/z 283 fragment that results from the loss of H 2 O, as confirmed by Smyth et al (2000). Another breakage that can occur is the loss of the CO that forms the m/z 255 fragment; such fragment was confirmed by Xiang et al (2011), Kim et al (2011 and Rust et al (2012), in their analysis of hair samples; the results were similar to those obtained by Smink et al (2004) in whole blood samples.…”
Section: Identification Of Metabolitessupporting
confidence: 64%
See 1 more Smart Citation
“…On the basis of the proposed fragmentation pathway for the metabolite temazepam m/z 301.0, it is possible to form the m/z 283 fragment that results from the loss of H 2 O, as confirmed by Smyth et al (2000). Another breakage that can occur is the loss of the CO that forms the m/z 255 fragment; such fragment was confirmed by Xiang et al (2011), Kim et al (2011 and Rust et al (2012), in their analysis of hair samples; the results were similar to those obtained by Smink et al (2004) in whole blood samples.…”
Section: Identification Of Metabolitessupporting
confidence: 64%
“…However, Smyth et al (2010) reported that this loss of water (from the benzodiazepine ring) causes the contraction to a six-membered ring. As a result, there is a loss of CO, which forms the m/z 241 fragment and chlorine, with the formation of m/z 206, as confirmed by Smyth et al (2000), Smink et al (2004) and Kim et al (2011). Another possible route is the formation of m/z 241 through the loss of a phenyl group, resulting in the formation of a Fig.…”
Section: Identification Of Metabolitesmentioning
confidence: 97%
“…Many efforts have been researched to detect the flunitrazepam by indirect laser-induced fluorescence detection on a microfluidic device 12 , GC/MS, or HPLC from specimen testing: body fluid, hair, etc. [13][14][15][16][17][18][19][20][21][22] Although the detection of flunitrazepam by these techniques is a precise quantitative analysis, the sample preparation is complicated, time consuming, and expensive. It would be an advantage to screening flunitrazepam readily from alcoholic drinks by a simple technique like UV-Vis absorption spectrophotometry owing to its convenient sample preparation, low cost, and fast detection.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes a poorly adapted dosing of these drugs can worsen the patient status due to their eventual toxicity and this is particularly the case for tricyclic antidepressants, barbiturates and first generation antipsychotics. Moreover, due to their widespread use, psychotropic drugs are frequently involved in cases of deliberate and accidental poisoning (Sanchez De La Torre, Martinez, & Almarza, 2005;Smink et al, 2004). So far in Rwanda, the determination of BCLs of these drugs is not done regardless of the case.…”
Section: Introductionmentioning
confidence: 99%